The depth distribution of the absorbed dose of the electron beam in the tissue-equivalent medium; Методология проектирования молодежного научно-инновационного пространства для российской энергетики - Miloichikova I. A. Irina Alekseevna (Nuclear technologies as integral part of engineering sciencein the modern world, 2013)
Заглавие с экрана